Combination Laser Interstitial Thermal Therapy Plus SRS Increases Time to Progression for Recurrent SRS-Treated Brain Metastases. (16th November 2020) - Grabowski, Matthew M; Sankey, Eric W; Srinivasan, Ethan; Griffin, Andrew; Otvos, Balint; Olufawo, Michael; Scott, Alex; Kim, Albert H; Leuthardt, Eric C; Barnett, Gene H; Mohammadi, Alireza M; Fecci, Peter E
Abstract: INTRODUCTION: Improved survival among patients with brain metastases (BM) has been accompanied by a rise in tumor recurrence after stereotactic radiosurgery (SRS). Laser interstitial thermal therapy (LITT) has evolved as an effective treatment for SRS failures, and an alternative to open resection or repeat SRS. METHODS: A multicenter, retrospective study was performed of patients who underwent treatment for biopsy-proven BM recurrence after SRS. Patients were stratified by planned LITT+SRS vs. LITT alone vs. repeat SRS. Index lesion progression was determined by RANO criteria. RESULTS: Forty-five patients fit inclusion criteria, with a median follow-up of 7.3 months (range:1.1-30.5), age of 60 (range:37-86), KPS of 80 (range:60-100), and pre-procedure contrasted tumor volume (preCTV) of 6.1cc (range:1.4-19.4). Primary diagnoses included NSCLC (44%), breast (24%), SCLC, melanoma, colon, and oroesophageal (<10% each). Sixty-three percent of patients underwent LITT alone, 18% had repeat SRS, while 27% had LITT+SRS (post-LITT SRS). Median time to index lesion progression was greatest in the LITT+SRS group compared to LITT alone or repeat SRS (>23, 7.5, and 3.6 months, respectively [ P  = .018), as was overall survival (23.7, 5.9, and 7.0 months, respectively [ P  = .023). Age, sex, primary histology, preCTV, and treatment strategy were univariate predictors of tumor progression. Blue TDT line ablation coverage was predictive of progression with LITT alone, but not with LITT+SRS. In a univariate model, patients not treated with LITT+SRS were significantly more likely to have index lesion progression ( P  = .016). When controlling for tumor histology and preCTV in a multivariate model, patients not treated with LITT+SRS were significantly more likely to have index lesion progression ( P  = .001). All patients undergoing LITT+SRS who experienced subsequent progression were diagnosed with recurrent tumor, while the radiation necrosis incidence in the repeat SRS arm was 25%. CONCLUSION: These data suggest that LITT+SRS is superior to LITT alone or repeat SRS for treatment of biopsy-proven BM recurrence after SRS, when controlling for other variables known to be predictive of progression. Prospective trials should be designed to further validate the utility of combination LITT+SRS after SRS failure.